Development of Health Promoting Model among the Coast Community Older Adults - Kangchai, Waree (Journal of Nursing, Siam University, 2020)
This research was the research and development design which aimed to develop health promotion model for the elderly along eastern sea coast. The research was conducted in the selected areas in Chon Buri Province. The sample consisted of 200 persons comprising elderly, elderly caregivers, people and staff working with related agencies. Data were collected by the instruments which had acceptable validity and reliability. Data were analyzed using descriptive statistics and t-test. Results revealed that the health promotion model for elderly along eastern sea coast was holistic care consisted of six parts including 1) providing knowledge about health promotion for elderly 2) developing essential skills for health promotion for elderly 3) providing knowledge about health promotion for elderly caregivers 4) building environment facilitating health promotion for elderly 5) building community strength and participation for health promotion for elderly 6) implementing continuous proactive activities for health promotion for elderly. These findings suggest that community should use the health promotion model for elderly along eastern sea coast from this study in order to conduct health promotion for elderly along eastern sea coast and should apply this health promotion model to the community along other sea coasts.